Back to the roots of ARPANET and Internet history with Alexandre Serres. Issue 1 (2nd January 2019) - Schafer, Valérie; Cooper, Sarah; Paloque-Bergès, Camille
Abstract: Alexandre Serres' PhD, "Aux sources d'Internet: l'émergence d'ARPANET" ("The origins of the Internet: the Emergence of ARPANET"), defended in 2000, is quite influential in Francophone research literature and discourse on Internet histories. However, yet untranslated, it has remained little known in Anglophone scholarly circles. The results of this thesis, which strongly echoes other articles and interviews, that are part of this special issue on ARPANET, remain still relevant and valid and we have chosen to introduce the reader to the final part of Serres' research – an inevitable choice within the 600 pages of this work